PENTINGNYA MEMBANGUN KOMITMEN KERJA SEBAGAI UPAYA MENINGKATKAN KINERJA MELALUI PENINGKATAN MOTIVASI, LINGKUNGAN, DAN KOMPENSASI - Fitria Nur Anggraeni (Inovasi, 2021)
This study aims to analyze and prove the effect of compensation, work discipline and work environment on work motivation, both partially and jointly, and the effect of compensation, work discipline, work environment and work motivation on organizational commitment, both partially and collectively. The research method used in this research is descriptive survey method and explanatory survey with a population of 1,339 employees and a sample size of 224 respondents, and the data analysis method used is SEM (Structural Equation Modeling). Based on the results of the study, then obtained the findings of structure I, compensation and work environment is partially significant effect on work motivation, while labor discipline no significant effect, but together all exogenous positive and significant effect on work motivation with the value of the contribution (R2) by 50%. Partially, the compensation variable has the most dominant influence on work motivation. In the second structure, compensation, work discipline, work environment and work motivation partially and jointly positive and significant impact on faculty commitment to the value of the contribution (R2)equal to 76%. Partially, the compensation variable has the most dominant influence on lecturer commitment. The work motivation plays a role as partial mediating, where the increase in lecturer commitment is influenced by compensation and the work environment is mediated by work motivation. Meanwhile, work discipline can have a direct effect on lecturer commitment even though they are not motivated.